Analysis of fundraising strategies at Amil Zakat Institutions (LAZ) Baitul Maal Hidayatullah (BMH) Bengkulu representative / Natasya Citra … [et al.] - Citra, Natasya (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Focus research is the performance of the LAZ BMH Bengkulu, the implementation and impact of implementing the fundraising strategy at the LAZ BMH Bengkulu, and the strategy to increase ZIS acceptance in future. it uses a qualitative method. The results showed that (1) the performance of LAZ BMH Bengkulu in 2022 experienced significant growth with a total of 3,498,356,116 funds collected from the previously determined target of 2,227,690,000 with a fixed number of donors reaching 500 people. (2) LAZ BMH Bengkulu apply two fun raising strategies, namely direct fundraising through social media such as Instagram, Facebook, etc, and the second strategy is indirect fundraising through collaboration with several zakat partners and attracting influential figures such as wawali. (3) Alternative strategies, namely: Establishing good relations with the community, increasing cooperation with zakat partners, Increasing socialization regarding the importance of zakat infak and shadaqah to the community.